2016
DOI: 10.11113/jt.v78.8328
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bioactive Compound From Moringa Oleiferaagainst Cancer Based on in Silico Screening

Abstract: Cancer is the leading cause of death in the world. More than 10 million people worldwide are expected to be diagnosed with cancer, a disease commonly believed to be preventable. Moringa oleifera is one of the well known as a local plant as food and health plant in Indonesia. Anticancer is one of potential treatment found in Moringa oleifera seed, leaves, and pods extracts. This study aimed to discover natural bioactivity compound from Moringa oleifera for anticancer. Niazimicin is one of bioactive compound fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Limited docking studies of NZ with potential enzymes have been reported in literature (Khusro et al., 2020; Pangastuti et al., 2016). To the best of our knowledge, this is the first report of in silico docking of NZ to its target enzymes, caspase‐3 and iNOS.…”
Section: Resultsmentioning
confidence: 99%
“…Limited docking studies of NZ with potential enzymes have been reported in literature (Khusro et al., 2020; Pangastuti et al., 2016). To the best of our knowledge, this is the first report of in silico docking of NZ to its target enzymes, caspase‐3 and iNOS.…”
Section: Resultsmentioning
confidence: 99%
“…The 3D structure of 12 active compounds from M. officinalis includes, Quadranoside-III (Pubchem ID: 10327092), Luteolin-7-glucoside-3′-glucuronide (Pubchem ID: 44258136), Melitric acid – A (Pubchem ID: 10459878), Labiatenic acid (Pubchem ID:5281792), Nepetoidin-A (Pubchem ID: 5316820), Salvianic acid-A (Pubchem ID: 11600642), (R)-Citronellal (Pubchem ID:75427), 5-Ketooctanoic acid (Pubchem ID:128859), Conhydrinone (Pubchem ID:426124), gamma-Coniceine (Pubchem ID:442632) and 5-Ketooctanal (Pubchem ID: 12538121) were retrieved from PubChem database [ 37 ]. Drug likeliness properties of ligands were analysed using Data Warrior tools for the selected active compounds [ 38 ] ( Figure 2 ).
Figure 2.
…”
Section: Methodsmentioning
confidence: 99%
“…The crystal 3D structure of the following active compounds of Cinnamon were retrieved from PubChem database (O'Boyle et al, 2011). Drug-likeliness properties of ligands were analyzed for the selected active compounds using DruLiTo software (Pangastuti et al, 2016).…”
Section: Preparation Of Ligands and Analysis Of Drug Likelinessmentioning
confidence: 99%